Holy Apparition or Hyper-Religiosity: Prevalence of Explanatory Models for Religious and Spiritual Experiences in Patients with Bipolar Disorder and Their Associations with Religiousness - Ouwehand, Eva (Pastoral psychology, 2020)
One point that emerges from qualitative research on religion and bipolar disorder (BD) is the problem patients with BD experience in distinguishing between genuine religious experiences and hyper-religiosity. However, clinical practice does not obviously address communication about differences in explanatory models for illness experiences. The aim of the current study is first to estimate the frequencies of different types of explanations (medical versus religious) for experiences perceived as religious and related to BD, second to explore how these types relate to diagnosis and religiousness, and third to explore the frequency of expectation of treatment for religiosity. In total, 196 adult patients at a specialist outpatient center for BD in the Netherlands completed a questionnaire consisting of seven types of explanations for religious experiences and several items on religiousness. Of the participants who had had religious experiences (66%), 46% viewed the experiences as part of spiritual development' and 42% as both spiritual and pathological,' 31% reported keeping distance from such experiences,' and 15% viewed them as only pathological.' Measures of religiousness were positively associated with part of spiritual development' and negatively associated with keeping distance from the experiences' and only pathological.' Half of the sample viewed religiosity as an important topic in treatment. It can be hypothesized that strength of religiousness may help people to integrate destabilizing experiences related to BD into their spiritual development. However, the ambiguity of strong religious involvement in BD necessitates careful exploration of the subject in clinical practice.